Biblical Background of Sacrament of Priesthood - Николай (Петров) Дякон (Forum Theologicum Sardicense, 2025)
Deacon Nikolay (Petrov), Biblical Background of Sacrament of Priesthood. The present research explores the Orthodox Christian understanding of the priesthood based on Scriptural texts. It examines not only the New Testament but also the Old Testament concept of priesthood and elucidates the mystical meaning of the Sacrament through the insights of the Church Fathers within a dynamic Christological perspective.